Black cowboys of rodeo : unsung heroes from Harlem to Hollywood and the American West - Cartwright, Keith Ryan (University of Nebraska Press, 2021)
""Black Cowboys of Rodeo" is a collection of one hundred years' worth of cowboy stories - set against the backdrop of reconstruction, Jim Crow, segregation, the civil rights movement, and eventually the integration of a racially divided country - told in firsthand accounts from the cowboys themselves"--